2009
DOI: 10.1161/strokeaha.108.542191
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Smoking Abstinence After First-Ever Ischemic Stroke

Abstract: Background and Purpose-Predictors of smoking abstinence in stroke survivors remain largely unexplored. The present study addressed the relationship between degrees of nicotine dependence and smoking abstinence 3 months after ischemic stroke. Methods-One hundred smokers with first-ever ischemic stroke were prospectively enrolled to the study. Correlates of nicotine dependence as well as sociodemographic and clinical characteristics were assessed during hospitalization.Smoking status was determined at 3-month fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…16 In the present study, smoking cessation has not been associated to female sex as was the case in other cited studies 16,19 nor to worse functional dependence. 18,19,34 With regard to the variables related to smoking history, our results agree with Sienkiewick et al, 35 in which people who had stopped smoking presented less urge to smoke. However, in contrast to this study, patients who had stopped smoking in the present sample were not found to have had a different level of tobacco consumption and less tobacco dependence as those who did not stop smoking during the follow-up period.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…16 In the present study, smoking cessation has not been associated to female sex as was the case in other cited studies 16,19 nor to worse functional dependence. 18,19,34 With regard to the variables related to smoking history, our results agree with Sienkiewick et al, 35 in which people who had stopped smoking presented less urge to smoke. However, in contrast to this study, patients who had stopped smoking in the present sample were not found to have had a different level of tobacco consumption and less tobacco dependence as those who did not stop smoking during the follow-up period.…”
Section: Discussionsupporting
confidence: 92%
“…16,19,25,35 At 1 year, lower percentages have been reported to those in the present study (30%) 34 as well as similar percentages (41.1%). 16 In the present study, smoking cessation has not been associated to female sex as was the case in other cited studies 16,19 nor to worse functional dependence.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Building motivation to quit smoking could be seen as a multidimensional process determined by biological, psychological, social, and economic factors [1,2,3,4]. Although smoking cessation is considered as one of the most effective methods of secondary stroke prevention [2,5], little is known about smoking habits in stroke survivors who were active smokers before stroke onset.…”
Section: Tablementioning
confidence: 99%
“…Although smoking cessation is considered as one of the most effective methods of secondary stroke prevention [2,5], little is known about smoking habits in stroke survivors who were active smokers before stroke onset. For example, reasons for quit attempts in stroke patients remain largely unexplored.…”
Section: Tablementioning
confidence: 99%